Angola : Public Expenditure Management and Financial Accountability - World Bank (Washington, DC, 2012)
One of the most salient features of Angola's public expenditure management and financial accountability framework is the coexistence of two parallel, but articulated, expenditure execution systems: the conventional system, coordinated by the National Treasury Directorate, and a non-conventional one centered around the national oil company Sonangol. A standard assessment of a country's fiscal framework would usually concentrate on the conventional system; the Public Expenditure Management and Financial Accountability Review (PEMFAR) goes one step further by assessing the workings of the non-conventional system as well as its articulation with the conventional one. The key finding is that the justification of the use of the non-conventional system is gone, and its maintenance is imposing heavy costs on the economy. The PEMFAR proposes accordingly the adoption of a two-pronged reform strategy aiming at: (i) strengthening the formal public financial management structures and tools; and (ii) phasing-out and eventually eliminating the non-conventional mechanisms.